Between now and yore: the history-writing in Eduardo Coutinho’s cinema - Cláudia Cardoso Mesquita (Galáxia, 2015)
Eduardo Coutinho’s contemporary cinema is marked by the interview as a dramatic form, as well as the register of the ongoing encounter between the director and his interviewees. However, this “art of the present”, as called by Consuelo Lins, implies a rarer, denser history-writing project. This paper explores this dimension of his work by comparing two lms that are 20 years apart in their making: Twenty years later (1984) and Metalworkers (2004). Their similarities and differences allow us to note, between past and present, mutual insights that Coutinho’s diachronic gesture brings about, which hypothetically constitutes “the present as history”.